Complexity Leadership Theory and its contribution to decentralized water management analysis and practice (International Journal of Scientific Research and Management (IJSRM), 2018)
Water management systems in the world have evolved considreably in the last three decades from the traditional "prediction and control"(Phl-Wostl, 2006. p49) approach to more integrative approaches.(Biswas,2004,@004, p24). Practioners in the discipline may find inspiration from a number of leadership approaches in the literature that include transformational, intgrative, collabroative and entrepreneurial leadership, inter alia(Meijerink, S.2011). Another recent and interesting addition to leaadership literature is found in Complexity Leadership Theory(CLT) as developed by UHl-Bien, Marion and Bill McKelvey(@007). It is premised on on seeking understanding on how organisations respond to pressures in the modern knowledge era, in the contemporary and current work environment as well as in evolving circumstances. The model draws from complexity science, which is the " study of the behaviour of large collections of ....simple, interacting units endowed with the potential to evolve with time"(Coveney, 2003, p.1058 cited in Uhl-Bien et al 2007, p.299). In this respect the central tenet behind Complexity leadership theory is the use of the concept of complex adaptive systems(CAS) where issues of leadership , which is understood as the capacity to influence others, are seen as not as positions of authority but roles, are entangled between members of an organisation and "can be enacted within everyinteraction between members"(Lichenstein and Plowman 2009, p.618). In unpacking the conceptual framework behind CLT, there a reflection on the dynamic relationship between the bureacratic, administrative functions of the organisations and the emergent, informal dynamics of complex adaptive systems(CAS).The current state of water management, given the competing demands of the biosphere and the socio-sphere are amenable to be relooked at using the CLT lens. The concept of adaptive water management of water resources(Pahl-Wostl, 2006,p.49) is reviewed in realtion to CLT. Key words: complexity theory, complex adaptive systems, creativity, learning and adaptive water management